Designing a cocoa dryer using air type solar system for rural farmers usage / Syed Muzzafar Shah Syed Mokhtar - Syed Mokhtar, Syed Muzzafar Shah (Faculty of Architecture, Planning and Surveying, 1989)
The design of solar cocoa dryer is presented in -this paper. Further details of this design are described in chapter 5.This design is a result of the modifying of the forced convectional drying system which had been built at the Mechanical Engineering Faculty, University of Nigeria. The dryer is suggested for the rural farmers' usage, so that they could build their own dryer from the information given by this paper,in order to produce high quality of dry cocoa beans at a lower maintenance cost.